PERAN KEPEMIMPINAN DALAM MENINGKATKAN PRODUKTIVITAS KERJA PEGAWAI PADA KANTOR LURAH LALOLARA KECAMATAN KAMBU KOTA KENDARI - Abdul Kadir; Muhammad Yusuf; Biben Warni (Universitas Halu Oleo, 2022)
The purpose of this study was to determine how the role of leadership in increasing employee productivity in the Lalolara sub-district, Kecamatan Kambu Kendari city. The type of research used is descriptive qualitative which describes the data obtained from the field, and the data obtained from the results of interviews with informants, namely: village heads, secretaries, personnel, staff, and the community. Then the data is analyzed and draw conclusions. The results of this study indicate that based on the results of the analysis and discussion that have been explained, that the leadership role in the Lalolara Lurah Office has been carried out well and full of responsibility, especially in determining the vision and mission of the Lalolara Lurah Office, which can be seen from three indicators, namely; The role of leadership as a search path, the role of the leader as a harmonic and the role of the leader as an empowerer of the three indicators have been carried out well and quite satisfactorily. Meanwhile, in the work productivity of employees using four indicators, namely: ability, improving the work achieved, morale, and self-development. of the four indicators, then based on the results of the study show that in improving the work results achieved is still not quite satisfactory